Influence of physical environment towards leisure time physical activity (LTPA) among adolescents - Abdul Latif, Rozita; Mohd Nor, Maizan; Omar Fauzee, Mohd Sofian; Ahmad, Abdul Razak; Karim, Faridah (Elsevier, 2012)
The purpose of this study is to identify the influence of physical environment towards leisure physical activities among adolescents. As many as 913 respondents aged between 13 to 17 years old from four districts (Seremban, Muar, Kota Star, Kuantan) in Peninsular Malaysia, were chosen through a layered cluster random sampling technique. The results show that the safety of the environment is in moderate level (busy road: M=3.51, SP=1.31; stray dog: M=3.46, SP=1.38; crime: M=3.23, SP=1.33) and it has no connection with the involvement of youth in LTPA (r=-0.01, p>0.05). It is also discovered that sports facilities limit them from undergoing physical activities during leisure hours. However, facilities are easy to be used (75%) by youth and this leads to a significant relationship with LTPA (r=0.10, p<0.05). The implication of research shows that physical environment is pivotal in order to increase the amount of youth involvement in overall free time physical activities. Thus, it is suggested that these physical activities can only take more of the teenagers’ time if they are carried out in environments which are creative, comfortable, safe and user-friendly.